2021
DOI: 10.1146/annurev-financial-110420-090352
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of State-Owned Investors: Sovereign Wealth Funds and Public Pension Funds

Abstract: State-owned investors (SOIs), including sovereign wealth funds and public pension funds, have $27 trillion in assets under management in 2020, making these funds the third largest group of asset owners globally. SOIs have become the largest and are among the most important private equity investors, and they are key investors in other alternative asset investments such as real estate, infrastructure, and hedge funds. SOIs are also leaders in promoting environmental, social, and governance policies and corporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
2
12
0
3
Order By: Relevance
“…A concise method of categorizing SWFs is by their investment objective. We follow the Global SWF method of classification (Megginson et al, 2021).…”
Section: Swf Organization Todaymentioning
confidence: 99%
See 3 more Smart Citations
“…A concise method of categorizing SWFs is by their investment objective. We follow the Global SWF method of classification (Megginson et al, 2021).…”
Section: Swf Organization Todaymentioning
confidence: 99%
“…These SWFs share characteristics with development banks, but rely primarily on equity investments while development banks make loans to projects or firms. Carney (2021) offers an alternative SWF classification scheme to Megginson et al (2021), though one also based on observed investment purpose. He categorizes SWFs into foreign exchange reserve funds, stabilization funds, pension reserve funds, and savings funds.…”
Section: Swf Organization Todaymentioning
confidence: 99%
See 2 more Smart Citations
“…Their assets grew at a compound annual growth rate of 12.2% from $830 billion in 1999 to $8.3 trillion in assets in 2020 with 41.1% of SWF assets allocated to listed equities (SWFI 2021). This growth outpaces contemporaneous growth in assets held by other major conventional institutional owners such as insurance companies, pension funds, and hedge funds (Megginson et al 2021). Consequently, SWFs are recognized as new geopolitical powerbrokers (Drezner 2008).…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%